The wireless spectrum : the politics, practices, and poetics of mobile media - Crow, Barbara A., 1960-; Longford, Michael; Sawchuk, Kim (Digital futures, 2010)
As evidenced by the clientele in any urban coffee shop, devices such as cell phones, BlackBerries, and Wi-Fi-enabled laptops have proliferated, particularly during the past ten years. The Wireless Spectrum explores how wireless technologies have modified both individual and public life, transforming our experiences of space, time, and place, while reshaping our day-to-day interactions. Bringing together visual artists, designers, activists, and communication and humanities scholars to reflect on mobile media, this collection engages a new terrain of interdisciplinary research. Interrogating these new forms of community and communication practices as they are emerging in Canada and around the world, the essays in The Wireless Spectrum ask how these new technologies transfigure subjectivities, creating new forms of social behaviour and provocative aesthetic practices.